TYPOLOGY OF AUTHOR’S MODELS OF ARTISTIC THINKING IN UKRAINIAN AND WESTERN EUROPEAN SOCIAL PHILOSOPHICAL AND SYMBOLIC DRAMA - Khorob S. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
In recent years, scientists have systematically studied the theoretical and historical literary foundations of Ukrainian and Western European symbolism. However, their artistic features in the dramatic and theatrical world, both in national and foreign cultures, have not yet been definitively revealed. One of the important factors of such research is the comparative-typological method in the study of this model of the author’s ideological and aesthetic thinking. Therefore, the proposed article aims to find out the peculiarity of the Ukrainian form of this modernist structure and its self-sufficiency in comparison with Western European analogues of the late 19th and early 20th centuries. Therefore, the comparative-typological method and the cultural-historical methodology become productive in this research. Actually, this is the novelty of the proposed literary study, which will definitely add a scientific touch to the identification of the national self-worth and self-identity of the author’s models of symbolism, in particular, based on the material of the analyzed social philosophical dramatic works. After all, our science has not carried out such a consistent and systematic analysis of the genre of the social philosophical symbolist play. Therefore, this study will be one of such literary attempts in the direction of comparative typological research. According to it, in fact, the practical significance of such a study follows: its results can be used to clarify the national model of symbolism, in particular, its self-sufficiency in Ukrainian dramatic and theatrical culture for historians of our writing and stage art, for writing scientific works on modernism as an aesthetic phenomenon, for further elucidation of the originality of the genre of Ukrainian social philosophical drama, for post-graduate students and doctoral students who study the problems of functioning of modernist types of artistic thinking in Ukraine and in Europe.